Peran Komite Sekolah Dalam Implementasi Manajemen Berbasis Sekolah - weny nuzula (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
The background of the research of the study is supported by the implementation of regional autonomy that has caused various changes in all people's lives. This change is necessary to do, such as encouraging the community’s participation in the implementation of government’s various programs, particularly in the implementation of school-based management. The goal is to improve the quality of national education. One way which can accommodate the views, aspirations, and explore the potential of society to achieve educational quality improvement at the unit level of education is through the school committee. The school committee is formed as a consequence of increasing the complexity of the school organization in order to maximize the role and contribution of the society, to contribute and to be responsible for the success of the education.